Relationship between bone quality and shrinkage in maxillary sinus augmentation using synthetic alloplast versus xenograft - Kudsi, Rachad; Dawson, Dolphus R.; Gonzalez, Octavio A.; Kutkut, Ahmad; Tucci, Michelle A.; Porras-Aguilar, Rosario; Momox, Ana Espinosa; Al-Sabbagh, Mohanad (Journal of periodontal & implant science, 2025)
This clinical study evaluated differences in bone quality within the maxillary sinus when either alloplast or xenograft material was applied. Twenty participants requiring lateral sinus approach augmentation for delayed implant placement were divided into 2 groups. The first group received a silica-calcium phosphate composite (SCPC) alloplast, while the second received a bovine bone xenograft (Bio-Oss). Cone-beam computed tomography (CBCT) was used to measure changes in bone height and area immediately after surgery and 5 months after augmentation. Picrosirius red staining of bone biopsies, obtained during implant placement, was analyzed under polarized microscopy. A MATLAB algorithm was used for analysis following image acquisition. CBCT measurements revealed a statistically significant reduction in linear bone height among xenograft recipients ( ≤0.001). This finding indicated greater resorption compared to the alloplast group, which exhibited no significant difference in bone height at 5 months following sinus augmentation. Furthermore, 40% of xenograft recipients displayed an absence of mineralized tissue formation, indicating a limited osteoconductive effect compared to the alloplast group, in which mineralized bone tissue was present in all samples. Polarized light microscopy and color intensity measurements of picrosirius red-stained bone biopsies revealed a significantly higher ratio of mineralized collagen I to collagen III in the newly formed bone for alloplast compared to xenograft recipients. Trichrome staining demonstrated collagen I mineralization with the presence of osteoblasts and osteocytes, indicating new bone formation. The newly formed bone in the alloplast group exhibited markers of maturation, including the formation of reversal lines, Haversian systems, and blood vessels. Resorption of the SCPC alloplast-grafted granules was also observed. The increased formation and maturation of new bone appear responsible for the preservation of bone height in alloplast group recipients.